Уроджений гіпотероз. Етіопатогенез, клініка, діагностика, лікування - Bolshova, O.V.; Samson, O.Ya.; Muz, V.A. (Ендокринологія | Endokrynologia, 2020)
Уроджений гіпотероз. Етіопатогенез, клініка, діагностика, лікування